Non-invasive monitoring of peripheral perfusion: an exploration of non-invasive peripheral perfusion monitoring for applications in research & healthcare - Blaxter, Laurence (2015)
The need for real-time, prognostic perfusion data has been widely recognised in clinical practice and academia. Perfusion, the volumetric blood low to tissue, is an important tool for haemodynamic monitoring, since perfusion adequacy is vital to tissue health. Perfusion can serve as both a diagnostic indicator and a fundamental research tool. However, lack of a low cost, easily applied, and non-invasive sensor technology capable of measuring peripheral perfusion in absolute volumetric units is clearly a major factor preventing the widespread clinical use of perfusion monitoring. This thesis explores and evaluates potential techniques for the non-invasive measurement of peripheral perfusion in absolute volumetric units. Following a review of applicable technologies, a small selection of complementary optical methods are selected for study based on economic and technology readiness arguments, and a series of volunteer studies conducted to evaluate these using both of the shelf and prototype apparatus.